Reductive Alkylation of Hydrazine Derivatives with α-Picoline-Borane and Its Applications to the Syntheses of Useful Compounds Related to Active Pharmaceutical Ingredients - Kawase, Yasushi; Yamagishi, Takehiro; Kato, Jun-ya; Kutsuma, Teruo; Kataoka, Tadashi; Iwakuma, Takeo; Yokomatsu, Tsutomu (Synthesis, 2014)
An efficient method for the direct reductive alkylation of hydrazine derivatives with α-picoline-borane has been developed to synthesize a variety of N-alkylhydrazine derivatives. This method provided N,N-dialkylhydrazine derivatives and N-monoalkylhydrazine derivatives upon fine-tuning of the substrates and the reagent equivalency in a one-pot manner. The method was applied to the synthesis of active pharmaceutical ingredients of therapeutic drugs such as isocarboxazid.
Keywords: alkylation; hydrazones; reduction; hydrazines; α-picoline-borane